A systematic review of the diagnostic accuracy of automated tests for cognitive impairment - Rabeea’h Aslam; Vickie Bates; Y Dündar; Juliet Hounsome; Marty Richardson; Ashma Krishan; Rumona Dickson; Angela Boland; Joanne Fisher; Louise Robinson; Sudip Sikdar (2018)
Objective The aim of this review is to determine whether automated computerised tests accurately identify patients with progressive cognitive impairment and, if so, to investigate their role in monitoring disease progression and/or response to treatment. Methods Six electronic databases (Medline, Embase, Cochrane, Institute for Scientific Information, PsycINFO, and ProQuest) were searched from January 2005 to August 2015 to identify papers for inclusion. Studies assessing the diagnostic accuracy of automated computerised tests for mild cognitive impairment (MCI) and early dementia against a reference standard were included. Where possible, sensitivity, specificity, positive predictive value, negative predictive value, and likelihood ratios were calculated. The Quality Assessment of Diagnostic Accuracy Studies tool was used to assess risk of bias. Results Sixteen studies assessing 11 diagnostic tools for MCI and early dementia were included. No studies were eligible for inclusion in the review of tools for monitoring progressive disease and response to treatment. The overall quality of the studies was good. However, the wide range of tests assessed and the non‐standardised reporting of diagnostic accuracy outcomes meant that statistical analysis was not possible. Conclusion Some tests have shown promising results for identifying MCI and early dementia. However, concerns over small sample sizes, lack of replicability of studies, and lack of evidence available make it difficult to make recommendations on the clinical use of the computerised tests for diagnosing, monitoring progression, and treatment response for MCI and early dementia. Research is required to establish stable cut‐off points for automated computerised tests used to diagnose patients with MCI or early dementia.